Characterization of a very-low-density lipoprotein (VLDL)-associated cytotoxic factor. - Chan, S. Y. (Nature Publishing Group, 1981)
A VLDL-associated cytotoxic factor was isolated from sera of pregnant rats and characterized. The inhibitory effect of this factor on the macromolecular synthesis of rat prostate adenocarcinoma cells (PA-III) was also examined. VLDL (Sf 20-400) was subfractionated by differential ultracentrifugal flotation and the Sf 100-400 fraction was associated with most of the oncolytic activity. Chemical analysis of serum VLDL at various stages of pregnancy indicated that the 4 major constituents of VLDL (protein, triglyceride, cholesterol, and phospholipid), and the cytotoxic titre, were increased significantly before parturition and restored to normal levels by 24 h post partum. The delipidation of lyophilized VLDL by n-heptane suggested that the cytotoxic component was associated with the neutral lipid core of VLDL. Kinetic studies of colony inhibition and the incorporation of radioactive thymidine and leucine into 10% TCA precipitates of PA-III cells showed that VLDL induced irreparable cellular damage during the initial 15 h of incubation. The cytotoxic activity of VLDL was not due to the association with PGF2 alpha, beta-oestradiol, progesterone, 25-hydroxycholesterol, or free fatty acids (oleic, stearic, palmitic, linoleic, linolenic and arachidonic acids), monopalmitolein, elaidyl and alpha-linolenyl alcohol. The role of this factor in host defence against neoplasia is discussed.